Implementation of Organizational and Pedagogical Conditions for the Introduction of Innovative Educational Technologies - Kenjayeva Diana Shermatovna (Researchparks Publishing, 2022)
The article describes issues based on implementation of organizational and pedagogical conditions for the introduction of innovative educational technologies. Considering the transition to a global information society and the development of knowledge, one can speak about the adequacy of education to the socio-economic needs of the present and future only if its modernization is based not only and not so much on organizational innovations, but on changes in essence - in the content and technologies of personnel training and preparation of scientific research. As a social institution that reproduces the intellectual potential of the country, education must have the ability to advance development, meet the interests of society, a particular individual and a potential employer.